The future of domestic water law: trends and developments revisited, and where reform is headed. Issue 3 (3rd April 2019) - Burchi, Stefano
ABSTRACT: A re-visitation of trends and developments in water legislation in the light of experience and new legislation from selected countries confirms the findings of prior stocktaking, while bearing out advances in many areas: achieving adaptability of regulatory water-allocation mechanisms; blending efficiency and equity of allocation; 'greening' of water laws; bridging the land–water divide; and giving customary and de minimis water rights their due. The human right to water, and access to justice, are emerging new trends. These, and the advances listed earlier, show the likely direction of future water law reform.